Reflection-Based Academic Supervision and Observation by School Principals to Improve Learning Quality in Elementary Schools (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study examines the implementation of reflection-based academic supervision and classroom observation conducted by school principals as a leadership strategy to improve learning quality in Indonesian elementary schools. Although reflective supervision has been widely discussed globally, its application in the Indonesian context particularly within the Merdeka Curriculum era remains limited and often procedural. This study addresses this gap by analyzing how reflective supervisory practices contribute to teachers’ professional development and instructional improvement. Using a qualitative case study design, the research involved one principal, one vice principal, and six teachers at SD Negeri 114 Sukarami Palembang. Data were collected through semi-structured interviews, classroom observations, and document analysis. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model, with triangulation and member checking ensuring credibility.Results show that reflection-based supervision implemented through structured pre-observation, observation, and post-observation stages enhanced teachers’ lesson planning, classroom communication, and participatory learning strategies. Teachers also demonstrated increased reflective awareness and more consistent learner-centered instruction. Documented improvements included thecompleteness of lesson plans (from 67% to 100%) and enhanced classroom interaction quality. Challenges included limited supervisory time and varied teacher digital literacy. The study concludes that reflective academic supervision provides an adaptive leadership model that integrates clinical supervision principles with school culture, supporting continuous professional development under the Merdeka Curriculum. Findings contribute to instructional leadership theory and offer practical guidance for sustainable supervision systems in primary education.